2023
DOI: 10.1177/21925682231170613
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Remodeling After Posterior Lumbar Interbody Fusion: Comparison of Three-Dimensional Porous Tantalum and Titanium-Coated Polyetheretherketone Interbody Cages

Abstract: Study Design Retrospective cohort study Objectives The criteria for determining completion of intervertebral stability after posterior lumbar interbody fusion (PLIF) remain controversial. Several new radiological indicators of bone growth and osteointegration have been established. We compared computed tomography (CT) findings related to osteointegration after PLIF with interbody cages of two different materials and designs. Methods We retrospectively analyzed data from 103 patients who underwent PLIF with thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Thus, PTCs could be a viable alternative to autologous bone grafting, potentially avoiding donor-site morbidity. Furthermore, in posterior LIF (PLIF), PTCs show promising results in early bone integration and stability, as indicated by computed tomography (CT) findings of trabecular bone remodeling and lower incidences of vertebral endplate cyst formation compared with Ti-coated PEEK cages [ 49 ]. Collectively, these studies have suggested that PTCs can achieve immediate stabilization, facilitate bone fusion, and improve long-term outcomes in spinal surgery.…”
Section: Evolution Of Cage Materials In Lumbar Interbody Fusionmentioning
confidence: 99%
“…Thus, PTCs could be a viable alternative to autologous bone grafting, potentially avoiding donor-site morbidity. Furthermore, in posterior LIF (PLIF), PTCs show promising results in early bone integration and stability, as indicated by computed tomography (CT) findings of trabecular bone remodeling and lower incidences of vertebral endplate cyst formation compared with Ti-coated PEEK cages [ 49 ]. Collectively, these studies have suggested that PTCs can achieve immediate stabilization, facilitate bone fusion, and improve long-term outcomes in spinal surgery.…”
Section: Evolution Of Cage Materials In Lumbar Interbody Fusionmentioning
confidence: 99%